THE NATURE OF THE WESTERN TYPE OF AMERICAN ENGLISH (GA) AND THE SOUTHERN TYPE OF AMERICAN ENGLISH - Isakova Zarinabonu Alisher qizi (TADQIQOTLAR, 2025)
ABSTRACT This paper analyzes two principal varieties of American English: General American (GA), representing the western type, and Southern American English. The discussion centers on the phonetic characteristics that differentiate these dialects, specifically vowel systems, consonant realization, and prosodic features. Comprehending these variations is vital for phonetic research and for practical applications in language instruction.